Velocity and gas-void fraction in two-phase liquid-gas flow in narrow mini-channels - Sowiński, J.; Dziubiński, M.; Fidos, H. (Archives of Mechanics, 2009)
In the study, the values of velocity and gas void fraction in two-phase gas-liquid flow in narrow vertical mini-channels were experimentally determined. The influence of the physicochemical properties of liquid, the channel gap width and the superficial velocity of gas and liquid, on gas void fraction and gas bubble flow velocities in the flowing two-phase mixture in narrow, vertical mini-channels was investigated. The value of gas phase velocity was defined by means of a drift model, determining the values of distribution parameter C0. The relation describing the value of gas void fraction depended on the Bankoff coefficient and gas input volume fraction.